Crystalline phase transitions and water-soluble complexes of copper(I) 2-hydroxyethanethiolate. (1st August 2022) - Royappa, A. Timothy; Papoular, Robert J.; Gembicky, Milan; Shepard, William; Ross, Aubrey D.; Stemen, Audrey G.; Bobbitt, James J.; Doan, Duong T.; Lapidus, Saul H.; Johnston, Dean H.; Filatov, Alexander
Graphical abstract: Abstract: The coordination polymer copper(I) 2-hydroxyethanethiolate, (CuSCH2 CH2 OH) n, though insoluble in all common solvents, dissolved readily in basic aqueous solutions of the thiolate anion (HOCH2 CH2 S – ) of 2-mercaptoethanol to form a single species: the tetranuclear cluster [Cu4 (µ-SCH2 CH2 OH)6 ] 2– . From this solution were grown X-ray quality single crystals of copper(I) 2-hydroxyethanethiolate. This compound underwent a hitherto unknown crystal phase transition at ca. 6 °C, from point group P 21 21 21 to Pna 21, with noticeable changes in the geometry of the Cu-S layer and in the orientation of the alkylthiolate side chains. When the bulky base tetrabutylammonium hydroxide was employed in the aqueous thiolate solution used to dissolve (CuSCH2 CH2 OH) n, the water-soluble polynuclear copper(I) complex bis(tetrabutylammonium) hexakis(µ-2-hydroxyethanethiolato) tetracuprate(I), [(C4 H9 )4 N]2 [Cu4 (µ-SCH2 CH2 OH)6 ], could be isolated as X-ray quality crystals. Structural characterization of this complex revealed a tetrahedral arrangement of copper(I) centers with thiolates bridging the edges of the tetrahedra. On standing, this complex degraded to a larger polynuclear Cu(I) sulfide cluster.